2017
DOI: 10.1038/nplants.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

A single-nucleotide polymorphism causes smaller grain size and loss of seed shattering during African rice domestication

Abstract: Grain size is one of the most important components of grain yield and selecting large seeds has been a main target during plant domestication. Surprisingly, the grain of African cultivated rice (Oryza glaberrima Steud.) typically is smaller than that of its progenitor, Oryza barthii. Here we report the cloning and characterization of a quantitative trait locus, GL4, controlling the grain length on chromosome 4 in African rice, which regulates longitudinal cell elongation of the outer and inner glumes. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 36 publications
2
119
0
Order By: Relevance
“…A comparison of the re-acquisition of the seed dispersal mechanisms of rice and wheat may help to clarify this issue. Cultivated rice is diploid, and several seed shattering-related genes have been cloned in diverse backgrounds, including qSH1 (Konishi et al, 2006), OsCPL1 (Ji et al, 2010), SHTA1 (Zhou et al, 2012), OsSH1 (Lin et al, 2012), SH5 (Yoon et al, 2014), GL4 (Wu et al, 2017), SH3 (Lv et al, 2018) and SSH1 (Jiang et al, 2019). A complex network regulating seed shattering has gradually emerged.…”
Section: Comparison Of the De-domestications Of Rice And Wheatmentioning
confidence: 99%
“…A comparison of the re-acquisition of the seed dispersal mechanisms of rice and wheat may help to clarify this issue. Cultivated rice is diploid, and several seed shattering-related genes have been cloned in diverse backgrounds, including qSH1 (Konishi et al, 2006), OsCPL1 (Ji et al, 2010), SHTA1 (Zhou et al, 2012), OsSH1 (Lin et al, 2012), SH5 (Yoon et al, 2014), GL4 (Wu et al, 2017), SH3 (Lv et al, 2018) and SSH1 (Jiang et al, 2019). A complex network regulating seed shattering has gradually emerged.…”
Section: Comparison Of the De-domestications Of Rice And Wheatmentioning
confidence: 99%
“…Meanwhile, qLGY3 encodes the MADS-domain transcription factor OsMADS1, which is associated with long and slender grains resulting from increased cell division in a longitudinal direction in the outer epidermis (Liu et al, 2018). GL4 encodes a MYB-like transcription factor and controls grain length by regulating longitudinal cell elongation in the outer and inner glumes in African rice (Wu et al, 2017). Moreover, the OsGBP1 transcription factor represses grain length while OsGBP3 enhances grain length (Gong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies reported that the non‐shattering characteristic resulted from the selection of different sh4 mutant alleles in domesticated of both Asian and African rice (Lin et al ., ; Wu et al ., ). In the present work we found that the transition of plant architecture from the prostrate growth of wild rice to the erect growth of cultivated rice also resulted from the same locus during Asian and African rice domestication.…”
Section: Discussionmentioning
confidence: 97%
“…Crop domestication is the process of genetic reshaping of wild species to meet human needs (Doebley et al ., ). Several morphological characteristics, such as plant architecture, seed size and dispersal, have been changed during domestication (Tan et al ., ; Lin et al ., ; Pourkheirandish et al ., ; Wu et al ., ); this has been called ‘domestication syndrome’. The identification of genes controlling domestication‐related traits will provide insight into the rules of parallel domestication of crops (Paterson et al ., ; Meyer and Purugganan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation